KEPASTIAN HUKUM DALAM PENGATURAN KEWENANGAN NOTARIS DALAM PEMBUATAN AKTA RISALAH RAPAT UMUM PEMEGANG SAHAM PERSEROAN TERBATAS SECARA ELEKTRONIK: LEGAL CERTAINTY IN ARRANGEMENT OF NOTARY AUTHORITY IN ELECTRONIC MAKING OF DEEDS OF GENERAL MEETING OF SHAREHOLDERS OF LIMITED COMPANIES - Sisca Junia Azrin (JURNAL HUKUM DAS SOLLEN, 2023)
This study aims to find out and analyze the arrangements for making the minutes of the General Meeting of Shareholders held electronically in the perspective of laws and regulations. Then to find out and analyze the implementation of making the minutes of the General Meeting of Shareholders held electronically on the principle of legal certainty (ius constituendum). The formulation of the problem in this study is: how is the arrangement for making the minutes of the General Meeting of Shareholders held electronically in the perspective of laws and regulations? and how is the implementation of making the minutes of the General Meeting of Shareholders held electronically on the principle of legal certainty (ius constituendum)? This study uses a normative juridical method by researching and analyzing library materials such as primary data, namely laws and regulations with the help of secondary data sources or written materials in the form of articles, books, magazines and newspapers, as well as tertiary data in the form of the Big Indonesian Dictionary. and the Legal Dictionary. The approach used in this research is a statutory approach, and a conceptual approach.